Multiple‐Stimulus‐Responsive Supramolecular Gels of Two Components and Dual Chiroptical Switches. Issue 3 (13th November 2014) - Miao, Wangen; Qin, Long; Yang, Dong; Jin, Xue; Liu, Minghua
Abstract A new class of L‐glutamic gelators, LG12(CH2)nCOOH, containing different lengths of methylene spacer were synthesized. It was found that the gelation ability of these compounds themselves was very weak. However, when another compound, p‐xylylenediamine (XEA), was introduced, the gelation ability was improved greatly. In particular, LG12(CH2)10COOH showed super‐gelation ability in the presence of XEA, which could immobilize almost all of the solvents except methanol. Moreover, the formed supramolecular gels even could be molded. Interestingly, some supramolecular gels of LG12(CH2)nCOOH and XEA could respond to multiple stimuli, such as heating, shaking, sonication, and acid/base. The studies of CD spectra suggested that the supramolecular chirality induced by self‐assembled chiral gelator molecules in gels could be tuned by the length of methylene spacer. In addition, the supramolecular chirality could be regulated as on/off by heating–cooling or external NH3/HCl. This would facilitate the development of dual chiroptical switches by temperature and acid/base.